Growth Response and Yield of Pakcoy (Brassica rapa L.) on Various Concentrations Liquid Organic Fertilizer of Jiringa Hulls [Phithecellobium jiringa (Jack) Prain Ex King] - Hardiansyah, Peri; Nurjanah, Uswatun; Widodo, Widodo (Akta Agrosia, 2019)
ABSTRACT Pakcoy (Brassica rapa L.) is a type of vegetable crop and one of the short-lived species needed by the body because it contains good nutrition. In order to meet the needs of pakcoy, it must also be balanced with the production level. One of the efforts to increase the production of pakcoy is the nutrient application of liquid organic fertilizer (LOF) from jiringa hulls. LOF can be absorbed by plants quickly rather than solid organic fertilizers and it does not damage soil structures such as synthetic chemical fertilizers. This study aimed to determine the optimum concentration of LOF on growth and production of pakcoy. The research took place at the Green House Laboratory of Agronomy, Faculty of Agriculture, University of Bengkulu. This research used Completely Randomized Design (CRD) with one treatment factor and repeated 5 times, each treatment unit included 3 potted plants. Treatment of LOF concentration, consisted of 5 levels: T0: LOF 0% (Control), T1: LOF 25%, T2: LOF 50%, T3: LOF 75%, T4: LOF 100%. The concentration of L0F 100% produce the best growth and production of pakcoy and has longest canopy (22,18 cm), highest number of leaf (15,86 strands), widest leaf width (34,26 cm2), highest fresh canopy weight (68,85 gram), highest total dry weight (6.92 grams), highest greenish leaves (48.48), and highest dried root weight (1.72 grams). Keywords: LOF, Jiringa Hulls, Pakcoy, Concentration